Pengaruh Kesadaran Wajib Pajak, Pengetahuan Peraturan Pajak, dan Penyuluhan Perpajakan terhadap Kepatuhan Pembayaran Pajak Transaksi E-Commerce - Aloisius Hama (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
Testing the intended effect for the taxpayer, knowledge of tax regulations, and tax counseling with transaction tax payment compliance for e-commerce actors is the purpose of this research. The research population involves E-commerce actors in the fashion sector who operate on Instagram social media accounts and are located in Surabaya. Multiple Linear Regression is the provision chosen in the data analysis model of this study because this study was designed to examine the influence of the independent variable with the dependent variable. The study results indicate that the growing awareness of taxpayers has a negative and insignificant effect on compliance with paying taxes for e-commerce actors. Knowledge of tax regulations partially found a significant positive effect on tax compliance for e-commerce actors. Then, other results show that partial tax counseling has a positive effect that is not considered significant on tax compliance for e-commerce players.